Swedens Laffer Curve: Taxation and the Unobserved Economy - Edgar L. Feige; Robert T. McGee (The Research Institute of Industrial Economics (IUI), 1983)
Recent research on the unobserved economy suggests that the phenomenon has important implications for both macroeconomic policy and public finance. This paper focuses attention on the public finance implications by developing a simple macro-model from which it is possible to derive a Laffer curve. The model reveals that the shape and position of the Laffer curve depend upon the strength of supply side effects, the progressivity of the tax system and the size of the unobserved economy. Using alternative parameterizations of each of these effects, it is possible to obtain rough empirical estimates of the Laffer curve for Sweden.
Keywords: E60; H20; 330; Taxation; Public finance; Laffer curve